Imaginary of the End, End of the Imaginary. Bazin and Malraux on the Limits of Painting and Photography - Cisneros, James (Cinémas, 2003)
AbstractThis article analyzes the differences between photography, painting, and briefly, digital images in terms of the institutional discourses that have been partially determinant of their respective visual regimes. In a comparative reading of Bazin and Agamben, the author first analyzes the question of ontology in relation to photographic technology’s relative autonomy in the production of the modern image, underlining its implications for the viewing subject’s agency in the modern image’s production. This is contrasted to Malraux’s imaginary museum, an institutional paradigm that harnesses photography’s uncanny doubling to maintain an instrumental conception of the medium.